The association of alanine aminotransferase and diabetic microvascular complications: A Mendelian randomization study - Bi, Yaru; Liu, Yanjing; Wang, Heyuan; Tian, Suyan; Sun, Chenglin (Frontiers in Endocrinology, 2023)
Aims: Alanine aminotransferase (ALT) is positively related to diabetes risk in observational studies, whereas Mendelian randomization supports a linear causal association. In contrast, the relationship between ALT and diabetic nephropathy, and diabetic retinopathy is counter-intuitive in observational studies. Furthermore, no MR study has examined their causal association. The study aimed to investigate whether genetically determined ALT has a causal effect on diabetic nephropathy and diabetic retinopathy. Methods: Genetic instruments of ALT were obtained from a recent genome-wide association study that included 437,267 individuals of European ancestry. Summary data of diabetic microvascular complications were derived from the FinnGen study (3,283 cases and 181,704 controls for diabetic nephropathy, and 14,584 cases and 176,010 controls for diabetic retinopathy, both were of European ancestry). Effect estimation and pleiotropy testing were performed using inverse variance weighted (IVW), MR-Egger regression, weighted median, and mode-based estimator methods. Results: Based on IVW, a 2-fold increase in genetically determined ALT level was positively associated with diabetic nephropathy (odd ratio, [95% confidence interval], 1.72 [1.25-2.36], P＜0.001) and diabetic retinopathy (1.37 [1.14-1.65], P < 0.001), but a null causal association in three pleiotropy robust methods, namely, MR-Egger, weighted median and mode-based estimator. Conclusions: With caution, we concluded that ALT plays no linear causal role in developing both diabetic nephropathy and diabetic retinopathy. Further investigations are required to test the hypothesis of a non-linear causal association.